Consumer Preference and Willingness To Pay For Local Orange of Rimau Gerga Lebong - Putri, Rani Revina; Nurmalina, Rita; Suprehatin (School of Business, Bogor Agricultural University (SB-IPB), 2023)
The increasing demand and consumption of oranges have led many local governments to participate in developing superior local orange varieties that are acceptable to consumers, such as the local orange variety called